The Implementation of Problem-Based Learning Model in Maze Game of Multimedia Learning for Vocational School Students - Rohendi, D.; Sutarno, H. (INVOTEC, 2018)
Research on the use of games in learning has been growing rapidly. However, the material delivery is still conventional, without considering any certain learning methods. Yet, the method in learning is a factor that determines the success of teaching. Therefore, the purpose of this research is to find out how the implementation of Problem Based Learning model in the development of maze game of multimedia learning used. Maze game of multimedia learning devel-oped was implemented to the students of vocational school students. The results showed that the implementation of Problem-Based Learning in maze game of multimedia learning is worthed and categorized as excellent accord-ing to not only validation of expert of subject matter and media, but also students’ response.